Impact of Excess Adiposity on Cardiorespiratory Fitness in Children and Adolescents with Kawasaki Disease - Guan-Bo Chen; Sheng-Hui Tuan; Yi-Ju Tsai; I-Ching Huang; I-Hsiu Liou; Ko-Long Lin (Life)
(1) Background: To assess the impact of excessive body fat on cardiorespiratory fitness (CRF) and coronary artery health in children and adolescents following acute Kawasaki disease (KD-CA). (2) Methods: A retrospective study of KD-CA patients (ages 8–16) who completed cardiopulmonary exercise testing (CPET) in the last five years. Participants were classified based on body mass index (BMI) and fat mass index (FMI) into normal and excessive adiposity groups. Coronary artery (CA) Z-scores were calculated using the Lambda-Mu-Sigma method, with peak VO2 Z-scores (peak VO2 Z-score) derived from a database of Hong Kong Chinese children and adolescents. Primary outcomes included peak VO2 Z-score, Max-Z (maximum CA Z-score), anaerobic threshold metabolic equivalent (AT MET), peak MET, and pulse oxygen. Statistical analyses were conducted to evaluate differences across groups. (3) Results: A total of 112 KD-CA patients were included (mean age: 11.71 ± 2.54 years). The mean peak VO2 Z-score was −0.63 ± 0.98. Participants with normal BMI and FMI had significantly higher pulse oxygen levels compared to those with excessive BMI and FMI (both p < 0.001). Additionally, those with normal FMI showed higher AT MET, peak MET, peak VO2 Z-score (p = 0.049), and lower Max-Z (p = 0.026) than excessive FMI participants. Boys, especially those with normal adiposity, had superior AT MET, peak MET, pulse oxygen, and Max-Z compared to girls. (4) Conclusions: Excessive adiposity in KD-CA patients is associated with reduced CRF and elevated Max CA Z-score. These findings highlight the need to monitor body composition to optimize cardiovascular health in this population.